Supporting the wounded: Parents of adolescents recovering from substance use disorder - Faith Mathibela; Jan Masombuka (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: The increase of adolescent substance use disorders (SUDs) around the world has a lot of negative effects on the parents and frequently degrades their quality of life. Substance use disorder is a critical issue recognised as a chronic, complex health and social condition. Parents of adolescents recovering from SUD may suffer significantly as a result of the wide range of negative emotions that come with having adolescents recovering from SUD. From the extant literature, there is little evidence of the strategies used to address the support needs of parents who carry the burden of adolescent SUD care.